The Impact of the Society of Critical Care Medicine's Flagship Journal: Critical Care Medicine: Reflections of Critical Care Pioneers. Issue 2 (20th January 2023) - Bartlett, Robert H.; Carlet, Jean; Cook, Deborah; Gattinoni, Luciano; Harvey, Maurene; Jacobi, Judith; Parker, Margaret M.; Sprung, Charles L.; Suter, Peter; Thompson, Ann; Vincent, Jean-Louis
Abstract : On the 50th anniversary of the Society of Critical Care Medicine's journal Critical Care Medicine, critical care pioneers reflect on the importance of the journal to their careers and to the development of the field of adult and pediatric critical care.